Birth Defects Associated with Prenatal Alcohol Exposure-A Review - Katarzyna Anna Dyląg; Florencia Anunziata; Gretchen Bandoli; Christina Chambers (MDPI AG, 2023)
Since the recognition of fetal alcohol syndrome, alcohol has been accepted as a human teratogen. However, little is known about the relation between prenatal alcohol exposure and the spectrum of associated major birth defects. The objective of this review was to summarize data on the association of major congenital abnormalities and prenatal alcohol exposure. We included all major birth defects according to ICD-10 classification. We found that the strongest evidence to date lies in the research examining herniation (gastroschisis and omphalocele), oral clefts (cleft lip with or without palate and cleft palate) and cardiac defects. There is less consistent evidence supporting the association between prenatal alcohol exposure and anomalies of gastrointestinal system, diaphragmatic hernia, genitourinary system and neural tube defects. We found no material support for PAE and choanal atresia, biliary atresia or clubfoot.